The syntax of (in)dependence - Safir, Kenneth J. (Linguistic inquiry monographs, 2004)
One of the most important discoveries of modern linguistic theory is that abstract structural properties of utterances place subtle restrictions on how we can use a given form or description. For the past thirty years, these restrictions have been explored for possible clues to the exact nature of the structural properties in question. In The Syntax of (In)dependence Ken Safir explores these structural properties and develops a theory of dependent identity interpretations that also leads to new empirical generalizations. These generalizations range across a wide class of empirical phenomena, including the distribution of crossover effects, bound variables in ellipsis, functional answers to questions, resumptive pronoun constructions, (anti- ) reconstruction effects, and proxy readings. Safir approaches these interpretive issues from the perspective that the structural properties of all natural languages reflect an innate linguistic capacity, as embodied in Universal Grammar (UG). This monograph explores the way a particular syntactic restriction imposed by UG limits the range of dependent identity interpretations that a sentence can have and hence the range of possible entailments it can have on the basis of these anaphoric interpretations. Although certain of these interpretations may be favored by manipulating a discourse, the work focuses on interpretive restrictions that cannot be repaired by discourse accommodation. More specifically, Safir's main proposal is dependent identity interpretations are restricted by a c-command prohibition and not by a c-command licensing condition--that c-command does not license dependencies but plays a role in ruling them out. Although cross-linguisitic discussion in the main text is very limited, Safir adds an appendix on scrambling and reconstruction that focuses on scrambling in Hindi.